2003
DOI: 10.1177/0306624x03251120
|View full text |Cite
|
Sign up to set email alerts
|

Substance Use, Health, and Mental Health: Problems and Service Utilization Among Incarcerated Women

Abstract: This article profiles self-reported substance use, health, and mental health problems among a sample of incarcerated women in Kentucky as well as lifetime service utilization. Findings indicate that a high percentage of women reported use of alcohol, cocaine, and multiple substances during the month before incarceration. In addition, participants reported common health problems such as dental, female reproductive, physical injuries, and mental health problems including depression and anxiety. Participants repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
105
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 28 publications
7
105
1
2
Order By: Relevance
“…Esse mesmo alto percentual foi encontrado em outro estudo 17 , o qual denota que 61,7% das mulheres reclusas apresentaram depressão ao longo da vida. Já outra pesquisa, em que foi aplicado o BDI II, apontou 18% de prevalência de sintomas depressivos clinicamente significativos e 68,6% apresentando disforia 18 .…”
Section: Associação Entre Variáveis E Sintomas Depressivosunclassified
“…Esse mesmo alto percentual foi encontrado em outro estudo 17 , o qual denota que 61,7% das mulheres reclusas apresentaram depressão ao longo da vida. Já outra pesquisa, em que foi aplicado o BDI II, apontou 18% de prevalência de sintomas depressivos clinicamente significativos e 68,6% apresentando disforia 18 .…”
Section: Associação Entre Variáveis E Sintomas Depressivosunclassified
“…3,4,11,[16][17][18][19] One study compared the oral health of present or former her oin addict inmates to non-drug addict inmates, 15 another evaluated the health of female former substance abusers. 20 Due to the heterogeneous nature of the studies in terms of study design, institution type (state vs federal, single sex vs mixed), setting and population, data have not been synthesised. Rather, Table 3 documents the study charac teristics and principal findings for the common outcome measures for the total sample.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…7,15,20,24 Where the ration ale for the obtained sample size was stated, this focused on the practicality of carrying out the study. One study employed stopping rules.…”
Section: Potential Biasmentioning
confidence: 99%
See 1 more Smart Citation
“…HIV/AIDS and other health complications are only further compounded by the lack of health care access prior to involvement with the criminal justice system. Previous research has shown that female offenders had limited health service utilization in the community and while incarcerated, women sought out medical services at a greater rate than men due to their increased medical needs (Pollock, 2002;Staton, Leukefeld, Logan, 2001;Staton, Leukefeld & Webster, 2003). As the U.S. attempts to eradicate health disparities and improve the health of all Americans, there would be benefit in examining its healthcare services provided to criminal justice involved women across the spectrum, those in a controlled and community environments.…”
Section: Health and Health Risk Behaviors Of Women Involved In The Crmentioning
confidence: 99%